2022
DOI: 10.1021/acs.jafc.1c06223
|View full text |Cite
|
Sign up to set email alerts
|

Avenanthramide C from Oats Protects Pyroptosis through Dependent ROS-Induced Mitochondrial Damage by PI3K Ubiquitination and Phosphorylation in Pediatric Pneumonia

Abstract: Oat containing rich β-glucan, polyphenols, flavonoids, saponins, alkaloids, and other substances shows good biological activities. Therefore, the present study aimed to uncover the possible mechanism and therapeutic effect of Avenanthramide C in lessening inflammatory responses in pediatric pneumonia. Pediatric pneumonia was induced by liposaccharide (LPS) for vivo model and vitro model. Macrophage was performed to determine the mechanism and effects of Avenanthramide C in pediatric pneumonia. NLRP3 activity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 48 publications
(84 reference statements)
0
19
0
Order By: Relevance
“…46 In clinical samples, various subtypes of AKT are frequently shown to be overexpressed and mutated. 47 AKT has been linked to pyroptosis and apoptosis in recent years, according to research 48,49 This study also showed that AFFL could reduce EGFR overexpression and inhibit AKT protein expression in H460 and A549 cells (Fig. 6A and B).…”
Section: Discussionmentioning
confidence: 71%
“…46 In clinical samples, various subtypes of AKT are frequently shown to be overexpressed and mutated. 47 AKT has been linked to pyroptosis and apoptosis in recent years, according to research 48,49 This study also showed that AFFL could reduce EGFR overexpression and inhibit AKT protein expression in H460 and A549 cells (Fig. 6A and B).…”
Section: Discussionmentioning
confidence: 71%
“…All mice were randomly assigned to experimental groups and then anesthetized using 50 mg/kg pentobarbital sodium. Mice in the sham group (n = 6) were injected with normal saline, and mice in the ALI model group (n = 10) were injected with LPS (2 mg/kg, Sigma‒Aldrich) for 24 h according to the literature ( Pu et al, 2022 ). The lung injury score and W/D rate were measured according to the literature ( Pu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Mice in the sham group (n = 6) were injected with normal saline, and mice in the ALI model group (n = 10) were injected with LPS (2 mg/kg, Sigma‒Aldrich) for 24 h according to the literature ( Pu et al, 2022 ). The lung injury score and W/D rate were measured according to the literature ( Pu et al, 2022 ). Mice in the Deh group (n = 10) received 12.5, 25, or 50 mg/kg Deh ( SMB00350 , ≥98% , Sigma‒Aldrich) or 1 mg/kg dexamethasone (Dex, D1756, ≥98% , Sigma‒Aldrich) for 24 h and then induced into the ALI model and 12.5, 25, or 50 mg/kg Deh for 24 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipopolysaccharide is the prime component of endotoxin and is considered as the most important pathogen resulting in lung inflammation and sepsis. [13][14][15] LPS activates a large number of inflammatory cells and induces pneumonia through a variety of signaling pathways. [16][17][18] In this study, we successfully constructed a pneumonia model using LPS, and confirmed the effects of GPF on this model.…”
Section: Gpf Could Improve Lps-treated Beas-2b Cell Viabilitymentioning
confidence: 99%